2017
DOI: 10.1007/s40195-017-0608-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of Pure Titanium Treated by Laser Surface Treatment Under Different Processing Parameters

Abstract: Advanced characterization techniques are utilized to investigate the effect of laser surface treatment on microstructural evolution of pure titanium (Ti). The results show that there are three distinctly different types of microstructure from surface to substrate in Ti samples, including phase transformation and solidification microstructure in zone I (melting zone); insufficient recrystallization grains with residual a martensitic plates in zone II (heat-affected zone, HAZ); fully recrystallization microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In work [7] Poulon-Quintin et al investigated the effect of Nd:YAG laser surface treatment of cast titanium on the microstructure and mechanical properties and they found significant enhancement of the mechanical properties, while a higher tensile strength and higher values of elastic modulus of titanium were also obtained. Can Huang et al [19] analysed the microstructural evolution of pure titanium treated by a Nd:YAG laser under different processing parameters and observed three distinctly different types of microstructure from the surface to the substrate in Ti samples, namely phase transformation and solidification microstructure in the melting zone, insufficient grain recrystallization with residual martensitic plates in the heat-affected zone, and a fully recrystallized microstructure in the base metal. The authors showed that the material in the melting zone had the highest hardness, while the material in the heat affected zone had the lowest hardness value due to the insufficiently recrystallized grains.…”
Section: Introductionmentioning
confidence: 99%
“…In work [7] Poulon-Quintin et al investigated the effect of Nd:YAG laser surface treatment of cast titanium on the microstructure and mechanical properties and they found significant enhancement of the mechanical properties, while a higher tensile strength and higher values of elastic modulus of titanium were also obtained. Can Huang et al [19] analysed the microstructural evolution of pure titanium treated by a Nd:YAG laser under different processing parameters and observed three distinctly different types of microstructure from the surface to the substrate in Ti samples, namely phase transformation and solidification microstructure in the melting zone, insufficient grain recrystallization with residual martensitic plates in the heat-affected zone, and a fully recrystallized microstructure in the base metal. The authors showed that the material in the melting zone had the highest hardness, while the material in the heat affected zone had the lowest hardness value due to the insufficiently recrystallized grains.…”
Section: Introductionmentioning
confidence: 99%